KEBERFUNGSIAN KELUARGA, KEBAHAGIAAN DI SEKOLAH, SELF-ESTEEM DENGAN BULLYING - Lutfi Arya; Wanda Rahma Syanti (Universitas Andalas, 2021)
Abstract. Bullying has become one of the most common violent behaviors among adolescents worldwide. The current study examined the relationship between family functioning, happiness at school, and self-esteem with bullying among adolescents. A total of 121 adolescents (45 males and 76 females) aged between 12 – 15 years were recruited through simple random sampling. The measuring instruments were the Family Functioning in Adolescence Questionnaire (FFAQ), School Children’s Happiness Inventory (SCHI), Self-Esteem Scale (SSC), and Multidimensional Peer Victimization Scale (MPVS). Data were analyzed with multiple correlation techniques. The results showed that family functioning, happiness at school, and self-esteem were simultaneously correlated with bullying with negative direction. These findings have shown the importance of the roles of family and school to prevent bullying acts among adolescents.